Segurança e saúde do trabalho em arquivo: um estudo a partir do Tribunal de Justiça do Estado do Pará - SOUZA, Fabricia da Costa (2018)
Analysis, from exploratory research and case study on the safety and health practices found in the public record of the Court of the State of Pará. The research was intended to highlight the importance of health and safety for the professional file and users of these holdings. It was initially discussed the safety standards and your relationship with the file environments. Later, discussed security practices made in the public court File in the State of Pará, from visits and interviews by the author on the site. Research realized that there are practices made at the institution on this subject, however adjustments and improvements should be made to improve the health situation in place.